THE INFLUENCE OF CUSTOMER ORIENTATION PERCEPTION AND SERVICE QUALITY TO CUSTOMER SATISFACTION ON MATAHARI DEPARTMENT STORE MANADO TOWN SQUARE - Legi, Christian M.; Tulung, Joy E; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2021)
Customer satisfaction is the level of a person's feelings after comparing the benefits of the product that customers feel with their expectations. To create customer satisfaction, a company must be able to meet the needs and desires of customers related to the product, services, and purchases.Â Perception of customer orientation and quality of service to customers are important for creating customer satisfaction. Customer orientation is a business culture where the organization is committed to be creative in creating superior value for customers sustainably, while the quality of service will help customers solve their problems in meeting their needs and expectations for the products needed.Â This study aims to determine (1) whether customer orientation has a significant effect on customer satisfaction, (2) whether service quality has a significant effect on customer satisfaction, and (3) whether customer orientation and service quality together have a significant effect on customer satisfaction at Matahari Department Store in Manado Town Square.Â Keywords: customer orientation, perception, service quality, customer satisfaction